Physical Properties of Edible Films from Pangasius catfish Bone Gelatin-Breadfruits Strach with Different Formulations - Santoso, Rian Adhi; Atma, Yoni (Department of Technology of Agricultural product (THP) Jambi University, 2020)
Abstract— This research aims to provide edible film made from fish bone gelatin of Pangasius catfish mixed breadfruit starch with different formulations. The study was carried out through three stages including breadfruit starch isolation, edible films fabrication and analysis of physical properties of resulted edible film such as thickness, water vapor transmission, tensile strength and percent of elongation as well as moisture content. Edible films which were formulated from fish bone gelatin of Pangasius catfish by breadfruit starch addition have thickness values ranged of ​​0.084-0.123 mm, 6.08 - 16.77% of moisture content, water vapor transmission of 1.07 - 1.60 g/ m²/hour, tensile strength of 0.245 - 1.186 MPa, and percent of elongation around 70 - 87.14%. The edible films from gelatin of Pangasius catfish bone with breadfruit starch addition have physical characteristic which fulfill the standard requirements issued by Japanese Industrial Standard (JIS) Keywords— edible film; biodegradable materials; fish gelatin;breadfruit starch; food packaging